The role of Japanese automakers in Asean - Hanny Zurina Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines existing literature regarding the automotive industry in ASEAN countries. There are two questions that this paper tries to answer.First, how has the automotive industry developed and what are the strategies used by the automakers to face the effects of globalization. Second, how have ASEAN countries intiated the investment of automobile manufacturers in their countries and what was the response from the industry players. In order to fill the research gap related to the role of the japanese automakers in Southeast Asian countries, we have attempted to clarify the issues and problems of trade agreements in ASEAN region only.The conclusion is that Japan and ASEAN could not depend on the ASEAN Free Trade Area (AFTA) because trade agreements signed between non-ASEAN countries are attracting the investment of multinational firms in their countries. THe liberalization in protected industries, such as the automotive industry, should be promoted to increase the competitiveness of local firms in ASEAN countries.